Characterizing the Piezosphere: The Effects of Decompression on Microbial Growth Dynamics - Cario, Anaïs; Oliver, Gina C.; Rogers, Karyn L. (Frontiers in Microbiology, 2022)
The extent to which the full diversity of the subsurface microbiome can be captured via cultivation is likely hindered by the inevitable loss of cellular viability from decompression during sampling, enrichment, and isolation. Furthermore, the pressure tolerance of previously-isolated strains that span surface and subsurface ecosystems can shed light microbial activity and pressure adaptation in these transition zones. However, assessments of the effects of elevated pressure on the physiology of piezotolerant and piezo sensitive species may be biased by high-pressure enrichment techniques. Here, we compared two high-pressure cultivation techniques – one that requires decompression of the whole cultures during sampling and one that employs the previously-described isobaric PUSH devices – to explore the effects of repeated decompression during incubations performed to characterize isolates from deep environments. Two model sulfate-reducing prokaryotes were used to test the effects of decompression/repressurization cycles on growth rates, cell yields, and pressure tolerance. The mesophilic bacterium Desulfovibrio salexigens was cultivated from 0.1 MPa to 50 MPa, and the hyperthermophilic archaeon Archaeoglobus fulgidus was tested from 0.1 MPa to 98 MPa. For both cultivation methods, D. salexigens showed exponential growth up to 20 MPa, but faster growth rates were observed for isobaric cultivation. Furthermore, at 30 MPa minor growth was observed in D. salexigens cultures only for isobaric conditions. Isobaric conditions also extended exponential growth of A. fulgidus to 60 MPa, compared to 50 MPa when cultures were decompressed during subsampling. For both strains, growth rates and cell yields decreased with increasing pressures, and the most pronounced effects of decompression were observed at the higher end of the pressure ranges. These results highlight that repeated decompression can have a significant negative impact on cell viability, suggesting that decompression tolerance may depend on habitat depth. Furthermore, sampling, enrichment, and cultivation in isobaric devices is critical not only to explore the portion of the deep biosphere that is sensitive to decompression, but also to better characterize the pressure limits and growth characteristics of piezotolerant and piezosensitive species that span surface and subsurface ecosystems.